2020
DOI: 10.3389/fenvs.2020.556942
|View full text |Cite
|
Sign up to set email alerts
|

Mammals Make Use of Cashew Plantations in a Mixed Forest–Cashew Landscape

Abstract: Heterogeneous landscapes harboring mosaics of natural habitat and agriculture are increasingly gaining conservation focus in the tropics. While research on cash crops such as coffee, rubber, and oil palm has led to an understanding of their role as supplementary habitats, such has remained limited in cashew plantations despite it being a cash crop of global significance. We conducted a study to understand the occurrence of terrestrial mammal species in a mixed forest–cashew landscape in the northern Western Gh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Many of them stated that the ongoing “ forest clearing ” and “ deforestation ” for cashew expansion meant that “ habitat is lost ” and this is bound to have negative effects in terms of crop depredation and human-wildlife conflict. Majority of respondents stated that they saw wild animals in agricultural lands and in their villages, and not just within forests, consistent with a camera-trapping study which showed that wildlife used cashew plantations as habitats [ 40 ]. However, farmers still planned on clearing private forests for cashew cultivation.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Many of them stated that the ongoing “ forest clearing ” and “ deforestation ” for cashew expansion meant that “ habitat is lost ” and this is bound to have negative effects in terms of crop depredation and human-wildlife conflict. Majority of respondents stated that they saw wild animals in agricultural lands and in their villages, and not just within forests, consistent with a camera-trapping study which showed that wildlife used cashew plantations as habitats [ 40 ]. However, farmers still planned on clearing private forests for cashew cultivation.…”
Section: Resultsmentioning
confidence: 58%
“…The Western Ghats has lost 33,579 km 2 of forest cover between 1920s and 2013, with conversion to plantations as the main driver of deforestation, followed by agriculture and land degradation [ 39 ]. Questions related to how cashew expansion occurs, how these farming systems operate, and how cashew affect forest cover in the Western Ghats are poorly studied and require urgent attention given that monoculture cashew plantations are on the rise in these landscapes [ 40 ] and forests in this region have significant biodiversity value [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…While no ‘pests’ like Parakeet species were found during this study, they have been known to forage on the cashew nut in other similar landscapes. Rege (2016) found that out of 11 species of large mammals in the forests, 9 were also found in the adjoining cashew plantations in the same Tillari landscape.…”
Section: Discussionmentioning
confidence: 97%
“…Past studies in cashew have looked at mammalian diversity (Rege 2016) human primate interactions (Hockings et al, 2012, 2013; Casanova et al, 2014), butterfly diversity (Vasconcelos et al, 2015; Mahata et al, 2019) and spider diversity (Bhat et al, 2013). However, there have been no studies on birds so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation